(untitled) (Iranian Journal of Kidney Diseases, 2015)
Immunoglobulin G4 (IgG4)-related kidney disease is a systemic autoimmune disease which characterized by elevated serum IgG4 and dense infiltration of IgG4-positive plasma cells into tubular interstitium. It can be a mimicker of acute renal insufficiency. We herein report a rare case of IgG4-related kidney disease as a cause of acute renal insufficiency.